2005
DOI: 10.1111/j.1523-1755.2005.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine in hepatitis B-associated membranous nephropathy

Abstract: HBV-related MN leads to ESRD in a significant proportion of patients before the advent of antiviral therapy. Lamivudine treatment improves renal outcome in HBV carriers with MN and evidence of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 28 publications
0
58
1
Order By: Relevance
“…However, the incidence of lamivudine-resistant HBV mutant strain is as high as 24 % in 1 year and 53 % in 3 years [35]. In addition, recurrence of proteinuria after cessation of lamivudine is another problem [3,36]. On the other hand, entecavir is more preferable in long-term use because of the lower incidence of drug-resistant mutation, which is reported as 1.2 % over 5 years [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the incidence of lamivudine-resistant HBV mutant strain is as high as 24 % in 1 year and 53 % in 3 years [35]. In addition, recurrence of proteinuria after cessation of lamivudine is another problem [3,36]. On the other hand, entecavir is more preferable in long-term use because of the lower incidence of drug-resistant mutation, which is reported as 1.2 % over 5 years [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lamivudine treatment showed a significant decrease in proteinuria and HBV DNA clearance in a year. Cumulative 3-year renal survival was 100 % [3]. However, the incidence of lamivudine-resistant HBV mutant strain is as high as 24 % in 1 year and 53 % in 3 years [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lamivudine, a type of cytosine nucleoside analogue, can effectively suppress RNA reverse transcriptase. A study Adefovir dipivoxil combined with a corticosteroid for HBV-GN 1405 by Tang et al 5 showed that 10 patients who were positive for HBsAg and membranous nephropathy, which was confirmed by renal biopsy, presented with a nephrotic syndrome and underwent treatment with lamivudine. The complete remission rates of 40% and 60% were attained in the 6th and 12th months, respectively; but the widespread application of lamivudine was limited in clinics due to its high tolerance and low HBeAg-negative rate.…”
Section: Discussionmentioning
confidence: 99%